Quiet in her bones - Singh, Nalini, 1977- (A Madness of Sunshine, 2021)
"In this gripping thriller set in New Zealand, New York Times bestselling author Nalini Singh takes you into the twisted world of an exclusive cul-de-sac located on the edge of a sprawling forest. My mother vanished ten years ago. So did a quarter of a million dollars in cash. Thief. Bitch. Criminal. Now, she's back. Her bones clothed in scarlet silk. When socialite Nina Rai disappeared without a trace, everyone wrote it off as another trophy wife tired of her wealthy husband. But now her bones have turned up in the shadowed green of the forest that surrounds her elite neighborhood, a haven of privilege and secrets that's housed the same influential families for decades. The rich live here, along with those whose job it is to make their lives easier. Andsomebody knows what happened to Nina one rainy night ten years ago. Her son, Aarav, heard a chilling scream that night, and he's determined to uncover the ugly truth that lives beneath the moneyed elegance...but no one is ready for the murderous secrets about to crawl out of the dark. Even the dead aren't allowed to break the rules in this cul-de-sac"--